2007
DOI: 10.1080/00071660701687688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E, age and sex on performance of Japanese quail. 1. Haematological indices and liver function

Abstract: 1. A trial was conducted to examine the effects of dietary vitamin E content, age and sex on haematological indices and liver enzymes of Japanese quails. A total of 800 1-d-old quail chicks were assigned at random into 4 equal groups and fed on starter and layer diets containing 0, 1, 5 or 10 times the NRC recommended supplements of vitamin E. No selenium was added to the basal deficient diets; the other diets were supplied with 0.2 mg selenium/kg diet. 2. The investigation covered the age span of 3 to 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The therapeutic use of antioxidant vitamins has gained considerable interest during the last decade. Previous animal and human studies showed that vitamin E might play a role in preventing the oxidation of polyunsaturated fatty acids in erythrocytes membrane (Elaroussi et al, 2007). In the present study our results reveal that a combination between vitamin E and insulin play a great role in ameliorating the lipid profile in the treated group in comparison with the fatty liver induced group (Table 1) Also, as several cytokines as well as ER stress (Kammoun et al, 2009) are involved in NAFLD fibrogenesis, they may represent potential targets (Albanis et al, 2006).…”
Section: Discussion:-mentioning
confidence: 99%
“…The therapeutic use of antioxidant vitamins has gained considerable interest during the last decade. Previous animal and human studies showed that vitamin E might play a role in preventing the oxidation of polyunsaturated fatty acids in erythrocytes membrane (Elaroussi et al, 2007). In the present study our results reveal that a combination between vitamin E and insulin play a great role in ameliorating the lipid profile in the treated group in comparison with the fatty liver induced group (Table 1) Also, as several cytokines as well as ER stress (Kammoun et al, 2009) are involved in NAFLD fibrogenesis, they may represent potential targets (Albanis et al, 2006).…”
Section: Discussion:-mentioning
confidence: 99%
“…The therapeutic use of antioxidant vitamins has gained considerable interest during the last decade. Previous animal and human studies showed that vitamin E might play an important role in preventing the oxidation of polyunsaturated fatty acids in erythrocytes membrane, thereby maintaining erythrocytes membrane integrity and inhibiting oxidative stress which leads to erythrocytes lysis [41] . Additionally, vitamin E was known to be the most effective natural lipid soluble chain-breaking antioxidant which scavenges free radicals, thereby preventing free radicals generation and reduce lipid peroxidation in erythrocytes membrane, resulting in decreased erythrocytes hemolysis and normalization of all hematological parameters [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Проте відмічено тенденцію до зменшення кількості лейкоцитів у крові пе-репілок у період статевого дозрівання (40-ва доба) та збільшення на початку яйцекладки, що підтверджує дані Elaroussi [20], який вважає, що такі зміни пов'язані з яєчною продуктивністю перепілок.…”
Section: результати та їх обговоренняunclassified